Shoot enlongation pattern in a provenaces test of Pinus greggii Engelm. at the Sierra of Arteaga, Coahuila - Valencia-Manzo, Salvador; Playas-Ramos, Ismael; Cornejo-Oviedo, Eladio H.; Flores-López, Celestino (Instituto de Ecología, A.C., 2017)
The shoot elongation pattern determines the type of height growth in a given species and little is known about the variation among its provenances, therefore, the objective of this study was to evaluate the variation of shoot elongation pattern among saplings of three provenances of Pinus greggii established at Los Lirios, Arteaga, Coahuila. Shoot elongation was measured every 15 days for two years (2007 and 2008); then, partial and accumulative growth was estimated for each measurement date. The results indicated that 54 % of total accumulative growth occurred from June to August in 2007 and 72 % occurred from May to July in 2008. The highest growth rates were 0.28 cm day-1 in May 2007 and 0.33 cm day-1 in June 2008. Significant differences were found among provenances for the accumulative growth only for eight dates in 2007 (P < 0.05). No differences were found in 2008 neither for the accumulative growth nor for the partial growth. The period of total shoot elongation, in the tree saplings of P. greggii, lasted 145 days and 197 days for 2007 and 2008, respectively; this represented 90% of the total shoot growth. Total shoot growth was strongly influenced by the favorable conditions of temperature and photoperiod that occurred in the summers of 2007 and 2008 at Arteaga, Coahuila.